PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA KORUPSI YANG MENJADI JUSTICE COLLABORATOR - Yulianus Marampa Rombeallo; Asher Tumbo (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2021)
Justice Collaborator is an actor who is willing to be a witness to open a clarity of an organized criminal act. Normative juridical sourced primary and secondary and tertiary materials, as well as the type of empirical juridical research which was analyzed qualitatively by describing descriptively the results of the existing data. To cooperate with law enforcement in finding evidence from other significant suspects so that investigations and examinations can run smoothly. Therefore, legal protection for justice collaborators is very important because it is feared that there will be potential threats from other actors, also so that all regulations related to justice collaborators do not overlap with each other and can unite perceptions among law enforcers related to corruption crimes organized.